Photography : A Very Short Introduction - Edwards, Steve (Oxford Oxford University Press, 2006)
Photographs are an integral part of our daily lives - from snapshots and tabloid newspapers to art photography in galleries and exhibitions. Edwards combines a sense of the historical development of photography with an insightful analysis of its purpose and meaning within a wider cultural context.
Include Illustrations and Index.
A Very Short Introduction.
Keywords: Photography -- Photographs